The Mediating Role of Innovation between Transglobal Leadership and Organizational Performance in Islamic Higher Education - El Junusi, Rahman; Mubarok, Ferry Khusnul (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
This study aims to examine the effect of transglobal leadership on organizational performance mediated by innovation. This research was conducted on 236 lecturers and academic staff of Islamic higher education. The data collected through the survey was applied to structural equation modeling (SEM) using AMOS. From the study, it was found that transglobal leadership significantly affects innovation and organizational performance, and innovation significantly affects organizational performance. Thus, this study contributes to the literature on the role of transglobal leadership and innovation in improving organizational performance. The originality of this study is to offer a transglobal leadership style that influences organizational performance in Islamic higher education that is mediated by innovation. Thus, there have been no studies investigating this causality.